Applying Business Strategies to Establish Your Research Program. Issue 20 (21st February 2020) - Nguyen, Thi A.; Nguyen, Andrew D.
Abstract: This article provides an overview of foundational concepts of business strategy and business development that scientists can apply to starting and expanding their research programs. It covers topics including: defining a value proposition, identifying stakeholders, considering research gaps, strategic collaborations, responsible hiring, strategic planning, and time management. © 2020 by John Wiley & Sons, Inc.